Communicating social security reform - Andrew Caplin; Eungik Lee; Søren Leth-Petersen; Johan Sæverud (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2022)
Despite its centrality in monetary policy, communication is not a focus in social security reform. We investigate the potential for active communication to dissipate apparently widespread public confusion about the future of social security. We implement a simple information treatment in which we randomly provide survey respondents access to the longevity-based eligibility age implemented by reform that Denmark launched in 2006. Absent treatment, younger workers not only have biased beliefs, expecting to become eligible for social security earlier than policy makers intend, but also are highly uncertain about eligibility age. The information treatment eliminates the bias, suggesting it results from misunderstanding. Yet it has no influence on uncertainty, suggesting this is driven by unavoidable demographic and political uncertainties. Our results highlight the value of communication strategies and belief measurement as policy instruments outside the monetary policy arena.
Keywords: D8; H55; J26; 330; social security; belief updating; information treatment; policy uncertainty